Near Real-Time Data in Support of National Fisheries Strategy in Timor Leste - CGIAR Platform for Big Data in Agriculture (2021)
The PeskAAS system was used to provide data for drafting of the new fisheries strategy and law, and is now integrated into fisheries management decision-making.